Relationship between proton pump inhibitors and adverse effects in hemodialysis patients: a systematic review and meta-analysis - Yuhan Zhang; Dawei Deng; Rongzhi Zhang; Jing Yi; Jianli Dong; Liyan Sha (Karger Publishers, 2022)
Background：Currently, the interaction between proton pump inhibitors (PPI) and their effects on hemodialysis (HD) patients has not been clarified. Here, we aimed to explore the association between PPI and adverse outcomes in HD patients. Methods：A search was performed on the PubMed, Embase, Cochrane Library, and Web of Science databases for relevant articles published up to April 10, 2022. Studies examining the association (odds ratio [OR]) between PPI and side effects were identified. The study followed guidelines prescribed in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), and was registered with PROSPERO (CRD42021291177). Results: A total of 12 studies comprising 4,227,497 HD patients with PPI were identified. Results showed that PPI use was associated with increased risk of bone fracture and hip fracture in the HD patients (pooled OR = 1.29, 95% CI = 1.21-1.37, p<0.00001, I2=0%; pooled OR = 1.37, 95% CI = 1.12-1.67, p=0.002, I2=82%). Besides, HD patients who received PPI were more likely to develop hypomagnesemia compared with those who did not receive PPI (pooled OR = 2.79, 95% CI = 1.95-4.00, p<0.00001, I2=0%). In addition, PPI use was linked to abdominal aortic calcification and all-cause mortality (pooled OR=2.03, 95% CI=1.28-3.24, p =0.003, I2=0%), (pooled OR = 1.44, 95% CI = 1.17-1.78, p = 0.0006, I2=0%). Conclusions: Taken together, the present results demonstrate that PPI use in HD patients is independently associated with adverse reactions such as hip fracture, hypomagnesemia, abdominal aortic calcification, and all-cause mortality. Thus, the use of PPI in HD patients should be carefully evaluated and optimized.